Extrauterine Spread, Adjuvant Treatment, and Prognosis in Noninvasive Uterine Papillary Serous Carcinoma of the Endometrium: A Retrospective Multicenter Study. Issue 1 (1st January 2016) - Boyraz, Gokhan; Salman, Mehmet Coskun; Basaran, Derman; Ozgul, Nejat; Turan, Taner; Turkmen, Osman; Kimyon, Gunsu Comert; Ozkan, Nazli Topfedaisi; Cagan, Murat; Gungor, Tayfun; Meydanli, Mehmet Mutlu; Gungorduk, Kemal; et al.
Abstract : Objectives: The aim of this retrospective multicenter study was to investigate the frequency of extrauterine metastasis and to evaluate the importance of surgical staging and adjuvant treatment among patients with noninvasive uterine papillary serous carcinoma (UPSC) of the endometrium. Materials and Methods: A multicenter, retrospective department database review was performed to identify patients with UPSC of the endometrium who underwent surgical staging between 2000 and 2015 at 4 Gynecologic Oncology Centers in Turkey. Demographic, clinicopathological, and survival data were collected. Results: A total of 182 patients with primary UPSC of the endometrium were identified. Of these, 33 (18.1%) had tumors limited to the endometrium with no myometrial invasion. Twenty (60.6%) of these 33 patients had no extrauterine involvement and International Federation of Gynecology and Obstetrics 2009 stage 1A disease was diagnosed after complete staging. The remaining 13 (39.4%) patients had disease beyond the uterine corpus including 5 with omental, 3 with adnexal, 1 with cervical stromal involvement, 1 with disease in the pelvic lymph nodes, and 1 with isolated para-aortic lymph node metastasis. Two patients had metastases in more than one location including omentum/adnexa/pelvic–para-aortic lymph nodes and omentum/pelvic–para-aortic lymph nodes, respectively. Of the 20 patients with disease confined to the endometrium, 6 (30%) patients received adjuvant treatment. Conclusions: Noninvasive UPSC has a high tendency for extrauterine spread and omentum is the most commonly involved location. Therefore, comprehensive surgical staging including omentectomy and pelvic–para-aortic lymph node dissection is mandatory in this group of patients. Risk of extrauterine spread is significantly associated with the presence of lymphovascular space invasion, elevated preoperative CA 125 levels, and positive peritoneal cytology. Adjuvant therapy for women with endometrium-confined disease improves neither progression-free survival nor overall survival.